2019
DOI: 10.1108/md-11-2017-1205
|View full text |Cite
|
Sign up to set email alerts
|

Board social capital reduces implied cost of capital for private companies but not of state-owned companies

Abstract: Purpose The purpose of this paper is to analyze how the type of ownership and control moderates the effect of the board social capital on the implied cost of capital. To do so, the authors analyzed the effect of the board social capital by the relational resources present in its direct and heterogenous ties, considering the predictions of analysts about the implied cost of capital. Design/methodology/approach The data panel comprised 137 companies listed on the Brazilian stock exchange between the years of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(103 reference statements)
1
5
0
Order By: Relevance
“…The resource dependence theory suggested that a director who is also a part of the board of other firms can bring resources into the firm (Hillman et al, 2000). It is consistent with the previous studies conducted by Goncalves et al (2019), and Fields et al (2012). Another important component of board activities is board attendance, which reflects efforts and intention of the board of directors to perform their duties, and reduce cost of capital (Lin, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The resource dependence theory suggested that a director who is also a part of the board of other firms can bring resources into the firm (Hillman et al, 2000). It is consistent with the previous studies conducted by Goncalves et al (2019), and Fields et al (2012). Another important component of board activities is board attendance, which reflects efforts and intention of the board of directors to perform their duties, and reduce cost of capital (Lin, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Studying the composition of directors is very imperative since the policy prescriptions for board structures in emerging markets may need to vary from developed markets due to different systems of governance (Levit & Malenko, 2016;Mbanyele, 2020). The study complements scanty literature on busy directors in emerging countries, China (Chen et al, 2014) India (Sarkar & Sarkar, 2009), Brazil (Goncalves et al, 2019) and some Asian countries (Kutubi et al, 2018). Increased studies on emerging markets enrich policy decision making in institutional environments with weak legal systems.…”
Section: Introductionmentioning
confidence: 81%
“…(4) Control variables. In our analyses, we control of other determinants that have been proven to effectively identify the effect of institutional investors on a firm's cost of capital [10,15,63,64]. These determinants are divided into two categories: financial variables and governance variables.…”
Section: Plos Onementioning
confidence: 99%
“…In 2010, the cost of capital started to be applied to evaluate senior executives of China’s state-owned enterprises by EVA (Economic Value Added), and in 2013, the proportion of EVA in evaluations was increased. Furthermore, an expanding body of academic research is analyzing the specific factors that influence the cost of capital [ 10 ]. However, relatively little is known about the influence on cost of capital by institutional investors in China’s capital market, since the size of institutional investors’ assets are growing fast, and the equity environment is undergoing distinct transformation under the recent reform of mixed ownership in China.…”
Section: Introductionmentioning
confidence: 99%